Optical absorption and refractive index of evaporated cadmium arsenide thin films in infrared region / Mahadzir Hj. Din - Hj. Din, Mahadzir (Unit of Research, Development and Commercialization (URDC),UiTM Perlis, 2004)
Measurements of transmission in the infrared showed interference maxima and minima from which the refractive index nr and the absorption coefficient a were determined. Values of refractive index of 5.3 and 5.6 were determined for films deposited under different conditions, and are reasonably consistent with each other in view of the differences in thickness and deposition temperature. The value of the absorption coefficient, a calculated was in the range of 10* (cm1) for film thickness 1.5 mm and substrate temperature, Ts at 300 K and it increases to in the range of 10s (cm1) for film thickness 0.46//m and substrate temperature 453 K. Some other samples showed the dependence of a on hv for a Cd3As2 film of thickness 0.24/im deposited onto a KCI substrate at a temperature of 300 K. These results are similar to those reported by Zdanowicz and Kwiecien (1977), having a value of a somewhat less than 10s cm1 for hv = 1 eV and falling to round 103 crrr1 below 0.1 eV.